Structural Validity of the Interpersonal Behaviors Questionnaire in Greek University Sport-Students (European Journal of Behavioral Sciences, 2024)
The examination of the interpersonal behaviors of undergraduate student-athletes can contribute to the research on the perceptions of students for satisfaction and frustration of basic psychological behaviors by teachers in the context teaching classes. Aim of this study was to translate into Greek and investigate the factorial validity and internal consistency of the Interpersonal Behavior Questionnaire (IBQ; 24-item six factors). 252 full-time undergraduate student-athletes (125 males and 127 females) were used ranging in age 18 to 38 years. The results of CFA showed a good fit of the data to the model, while the multi-sample results indicated invariance for factor loadings and correlations between male and female samples. Internal consistency coefficients Cronbach alpha and interclass correlation were moderate significant. In conclusion, the IBQ-Gr version has valid and reliable psychometric properties and can be applied to examination of the perceptions interpersonal behaviors others into Greek population.